2017
DOI: 10.1103/physrevb.96.104308
|View full text |Cite
|
Sign up to set email alerts
|

Coherent generation of symmetry-forbidden phonons by light-induced electron-phonon interactions in magnetite

Abstract: Symmetry breaking across phase transitions often causes changes in selection rules and emergence of optical modes which can be detected via spectroscopic techniques or generated coherently in pump-probe experiments. In second-order or weakly first-order transitions, fluctuations of the order parameter are present above the ordering temperature, giving rise to intriguing precursor phenomena, such as critical opalescence. Here, we demonstrate that in magnetite (Fe 3 O 4 ) light excitation couples to the critical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 58 publications
2
33
0
Order By: Relevance
“…b, Fourier transform of both curves in a. There are no features at higher energies where a previous study observed totally-symmetric optical phonon modes excited by 3.10 eV light[30]. Our THz probe is therefore only sensitive to the low-energy electronic collective modes reported here.…”
mentioning
confidence: 76%
“…b, Fourier transform of both curves in a. There are no features at higher energies where a previous study observed totally-symmetric optical phonon modes excited by 3.10 eV light[30]. Our THz probe is therefore only sensitive to the low-energy electronic collective modes reported here.…”
mentioning
confidence: 76%
“…The excitation of hot carriers can activate the additional phonon mode to participate in the THz absorption that are otherwise forbidden without photo excitation of hot carriers [72][73][74][75]. The studies of the phonon spectrum of Cd3As2 show that there are many low frequency optical phonon modes, such as A1g, B1g, B2g…”
Section: E T=0mentioning
confidence: 99%
“…[18][19][20][21] In magnetite, the equilibrium optical conductivity [22][23][24] shows a broad Drude peak in the metallic phase as well as its suppression at the metal-insulator transition. The optical properties at higher energies are dominated by two features peaking at about 0.6 eV and 2 eV.…”
Section: +mentioning
confidence: 99%